Identification of Tumor-Suppressive miR-30a-3p Controlled Genes: ANLN as a Therapeutic Target in Breast Cancer - Reiko Mitsueda; Ayako Nagata; Hiroko Toda; Yuya Tomioka; Ryutaro Yasudome; Mayuko Kato; Yoshiaki Shinden; Akihiro Nakajo; Naohiko Seki (Non-Coding RNA)
Our recently created RNA-sequence-based microRNA (miRNA) expression signature in breast cancer clinical specimens revealed that some miR-30 family members were significantly downregulated in cancer tissues. Based on TCGA database analyses, we observed that among the miR-30 family members, miR-30a-3p (the passenger strand derived from pre-miR-30a) was significantly downregulated in breast cancer (BC) clinical specimens, and its low expression predicted worse prognoses. Ectopic expression assays showed that miR-30a-3p transfected cancer cells (MDA-MB-157 and MDA-MB-231) had their aggressive phenotypes significantly suppressed, e.g., their proliferation, migration, and invasion abilities. These data indicated that miR-30a-3p acted as a tumor-suppressive miRNA in BC cells. Our subsequent search for miR-30a-3p controlled molecular networks in BC cells yielded a total of 189 genes. Notably, among those 189 genes, cell-cycle-related genes (ANLN, MKI67, CCNB1, NCAPG, ZWINT, E2F7, PDS5A, RIF1, BIRC5, MAD2L1, CACUL1, KIF23, UBE2S, EML4, SEPT10, CLTC, and PCNP) were enriched according to a GeneCodis 4 database analysis. Moreover, the overexpression of four genes (ANLN, CCNB1, BIRC5, and KIF23) significantly predicted worse prognoses for patients with BC according to TCGA analyses. Finally, our assays demonstrated that the overexpression of ANLN had cancer-promoting functions in BC cells. The involvement of miR-30a-3p (the passenger strand) in BC molecular pathogenesis is a new concept in cancer research, and the outcomes of our study strongly indicate the importance of analyzing passenger strands of miRNAs in BC cells.